Design and development of new perfluorodecalin-in-palm oil-in water delivery system for oxygen-enriched cosmeceutical skin care - Teo, Brian Sheng Xian (2014)
Cosmeceuticals, cosmetic-pharmaceutical hybrids, have gained much popularity in recent years due to the benefits it could provide to enhance health and beauty of the skin. In this research, a new colloidal delivery system was designed and developed to deliver oxygen into the skin while providing essential cosmeceutical actives. Oxygen, one of the most fundamental elements needed for sustaining life, is believed capable of maintaining epidermal health by facilitating the formation of collagen. Studies on the formation of simple emulsions were carried out to understand the fundamental characteristics of emulsions before the new colloidal delivery system was developed. Simple emulsions; perfluorodecalin-in-water (PFD/W) and palm oil esters-inwater (POE/W) were formulated to facilitate the studies. Due to larger difference in the interfacial tension between perfluorocarbons (PFCs) and water as compared to hydrocarbons (HCs) and water, PFD/W emulsions generally have bigger droplet size as compared to POE/W emulsions. Nonfluorinated surfactant, such as Lipoid S75 was employed to formulate PFD/W emulsions, and their droplet size ranged between 1 to 20 μm. Meanwhile, POE was emulsified using surfactant mixture of Tween 80 and Pluronic F-68 into water. They were characterised as POE/W nanoemulsions, owning droplet size ranged from 90 to 200 nm and possessed minimum rate of Ostwald ripening. Apart from that, DL-alpha-tocopherol acetate (vitamin E) and Pluoronic F-68 have proven to enhance the stability of POE/W nanoemulsions. Ternary emulsion, a novel complex emulsion was then developed from the simple emulsions formulated earlier. Ternary emulsion which consisted of three (3) immiscible phases was designed to deliver oxygen, lipophilic and hydrophilic cosmeceutical actives. The ternary emulsion was successfully formulated via a modified two-steps process, where PFD/W emulsion was added gradually into POE/W emulsion. The architecture of this ternary emulsions, determined using CytoViva® Hyperspectral Imaging System revealed that perfluorodecalin-in-palm oil esters-in-water (PFD/POE/W) ternary emulsion were formed. The PFD/POE/W ternary emulsions had an enhanced physical stability as compared to its parental emulsions. The in vitro studies showed that PFD emulsions were not toxic and had considerably facilitated the proliferation of human fibroblast cells. When tested on human subject, it showed potential increase in collagen content in the dermis layer upon completing two weeks of treatments. The best ternary emulsion to serve as a cosmeceutical skin care delivery system was found to be Formulation V15 consisting of 15% (w/w) PFD, 8% (w/w) POE, 19.8% (w/w) surfactant mixtures, 1% (w/w) Vitamin E, 1% (w/w) Kojic Acid, 1% (w/w) BHT, 1% (w/w) Phenonip and 53.2% (w/w) deionised water. Formulation V15 showed no physical separation during the accelerated as well as the long-term storage stability test. It not only had a high Ea value of 120.8 kJ K-1 mol-1 which indicated a strong resistance towards temperature stresses, but was also tested to have excellent shearthinning property (n = 0.1462) for the ease of spreading the formulation onto the skin. This formulation is capable of delivering multiple cosmeceutical actives such as antioxidants (Vitamin E), whitening agents (Kojic Acid) and oxygen, and can be considered as the most efficient formulation for use in effective cosmeceutical skin care products.